Ambient Noise-Based Mapping of Bedrock Morphology and Potential Fissure Zone in East Tanjung Karang, Bandar Lampung, Lampung, Indonesia - Ipmawan, Vico Luthfi; Permanasari, Ikah Ning Prasetiowati; Suhendi, Cahli (UI Scholars Hub, 2021)
As a business center and the most populous subdistrict, East Tanjung Karang in Bandar Lampung, Lampung, Indonesia, is considered an area with excessive groundwater exploitation. This activity can trigger ground fissures that can consequently cause damage to buildings and roads. In this study, microtremor recordings from 17 sites were collected and analyzed by using the horizontal to vertical spectral ratio and ellipticity curve method. Results showed that the ground profiles of shear wave velocity from 17 sites ranged from 143.5 m/s to 1752.46 m/s, and they could be used to determine sediment layer and its thickness based on the SNI 1726-2012 criteria. The thickness of the bedrock varied from 8.18 m to 117.18 m. Bedrock morphology was obtained by subtracting the sediment thickness from the altitude value. The bedrock morphology and slope were then used to construct a potential fissure map of the area between Y16 and Y17 and between Y26 and Y27, which had high bedrock slopes (more than 45°). The ground fissure potential in these areas was higher than that in other areas. Such areas also had a geological hazard potential from ground fissures caused by excessive groundwater exploitation. Our study could be used by authorities as a basis for preventing subsidence-related disasters in this subdistrict.